Worsening Proteinuria Following Intravitreal Anti-VEGF Therapy for Diabetic Macular Edema. (January 2019) - Kenworthy, Jessie-Anne; Davis, Justin; Chandra, Varun; Clark, J. Ben; Desmond, Michael
Intravitreal antivascular endothelial growth factor (anti-VEGF) therapy is a standard of care for a variety of ophthalmological conditions. While the systemic use of these agents in oncology is well known to induce a number of renal-related adverse effects such as worsening hypertension and proteinuria, the ability of local intravitreal injections to cause similar side effects has traditionally been thought to be unlikely given the lower doses used. In this case report, we describe an 88-year-old woman who developed a sudden worsening of her previously stable proteinuria with the use of bilateral intravitreal bevacizumab injections for diabetic macular edema, with improvement in her proteinuria upon reduction to unilateral therapy. This case report adds to the growing body of literature that suggests that local anti-VEGF therapy may have the potential to induce adverse systemic effects, and clinicians who care for these patients should remain vigilant to the development of potential renal-related toxicity.